Kinematics modeling and control simulation for a logging harvester in virtual environments - Yili Zheng (Advances in Mechanical Engineering, 2015)
This article presents the kinematics model and control simulation of a hydraulic boom. This hydraulic boom is used on the logging harvester, which is a typical forestry vehicle. The kinematics equations of the hydraulic boom and the transformation between joint variables and hydraulic cylinder variables are obtained for the control purpose. An autonomous control method is suggested for the harvesting head to capture trunks. There are two separate closed loops in the control scheme: the inner closed loop realizes the control on the hydraulic cylinders, and the outer loop plans the desired trajectory of the harvesting head to capture trunks based on the laser measurement data. An interactive real-time dynamic simulation system is developed, and the proposed control method is verified.